Kommentare. - Kunsthalle Wien; Matt, Gerald (Wien : Kunsthalle Wien NWV (Neuer Wissenschaftlicher Verlag) Wien - Graz, 2006)
Bechtold, Gottfried ; Beecroft, Vanessa ; Broodthaers, Marcel ; Cai Guo-Qiang ; Cattelan, Maurizio ; Fudong Yang ; Gappmayr, Heinz ; Jermolaewa, Anna ; Komar & Melamid ; Koons, Jeff ; Krystufek, Elke ; Kusama Yayoi ; Kusolwong Surasi ; Lum, Ken ; Margolles, Teresa ; Matelli, Tony ; McQueen, Steve ; Neshat, Shirin ; Rist, Pipilotti ; Rondinone, Ugo ; Sala, Anri ; Sierra, Santiago ; Smithson, Robert ; Tomic, Milica ; Tunick, Spencer ; Warhol, Andy
Duits
boek